(3cJGH GdSffs - (3SdjeGf Hf GdCTYK Hf ESMGb Hf HTjQ GdGROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s ((3eOjfI GdCScfOQjI s)
(3ChdgG (B:s
(3jHOC HHGH GdQLd jJOGhi s
(3BNQgG (B:s
(3jfJgi HHGH ai bJGd GddUhU s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYGJ YOjOI SfI (B637 (3g`s
(3hobQjA Ydi GdEeGe YHO GdeLjO Hf Odjds
(3GdejcQhajde ecQQ eQJjf OGNd GdYdHg GdhGMO s
(3jbhd GdcGJH ai BNQgbGHdJ LejYg HfSNI Gdabjg SfO Hf YfGQI GdCROi hbGHdI GdabjI ef fSNI GdWQWhTi s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs